Personalized Denture…Let’s make a difference!! -A clinical case report on characterized denture. - Shetty, Brijesh; Mody, Pranav V; Kumar, Manish; Kumar, Girish; Revankar Bhat, Kalpesh K. (Journal of Orofacial Research, 2011)
Despite the fact that solutions to functional and comfort problems are often available, successfully restoring the appearance of an edentulous patient remains a challenge. Esthetics pertains to the sense of the beautiful or the science which deduces from nature and taste the rules and principles of art. Esthetics has always exerted a profound influence in history. Because it has always been a prime concern of individuals, having the effect of exciting emotions of approval or disapproval. This case report differentiate a method of restoring esthetics for a 54 year-old male patient with completely edentulous maxillary and mandibular arches. Patient was treated with removable maxillary and mandibular conventional complete denture and characterized removable maxillary and mandibular complete denture. The results were significant with use of characterized denture compared to conventional denture were improvements in facial esthetics and more rapid social integration of this patient.